2014
DOI: 10.1158/1541-7786.mcr-13-0398
|View full text |Cite
|
Sign up to set email alerts
|

The Adherens Junction Protein Afadin Is an AKT Substrate that Regulates Breast Cancer Cell Migration

Abstract: The PI 3-K and Akt signaling pathway regulates all phenotypes that contribute to progression of human cancers, including breast cancer. Akt mediates signal relay by phosphorylating numerous substrates, which are causally implicated in responses such as cell growth, survival, metabolic reprograming and migration and invasion. Here we identify a new Akt substrate, the adherens junction protein Afadin, that is phosphorylated by Akt at Ser1718. We show that under conditions of physiological IGF-1 signaling and onc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 44 publications
5
50
0
Order By: Relevance
“…Intriguingly, we found that AF6 represses Snail expression depending on AF6's nuclear localization in PC cells. A similar phenomenon of AF6 nuclear localization also was observed when cells were exposed to growth factor signalling, and nuclear localization of AF6 may facilitate the induction of a transcriptional programme 14,[24][25][26] . However, there exists little evidence to show that AF6 can play a role as a transcriptional co-factor.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Intriguingly, we found that AF6 represses Snail expression depending on AF6's nuclear localization in PC cells. A similar phenomenon of AF6 nuclear localization also was observed when cells were exposed to growth factor signalling, and nuclear localization of AF6 may facilitate the induction of a transcriptional programme 14,[24][25][26] . However, there exists little evidence to show that AF6 can play a role as a transcriptional co-factor.…”
Section: Discussionmentioning
confidence: 52%
“…Accumulating evidence suggests that AF6 is a dual-residency protein, and its nuclear localization and transcriptional repressor activity are closely correlated 14,[24][25][26] . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Afadin has multiple functions in cell-cell adhesion and in cell movement, proliferation, survival and polarization (13). Afadin has also been demonstrated to regulate integrin-mediated cell adhesion and cell migration, although it appears that the function of Afadin in the positive or negative regulation of cell motility is context-dependent (14,15). Afadin also directly interacts with the tight junction-associated protein junction adhesion molecule-A, thereby affecting tight junction assembly during progression of the polarity program (16 The phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) pathway is a complex and central regulator of a number of fundamental cellular processes (17) and regulates all phenotypes that contribute to the progression of human cancer, including GBM (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of discordance between the gene and protein expression levels of occludin (56) support the theory that post-translational modifications of occludin may alter its expression in different tissues, the modifications of which have previously been comprehensively reviewed (53).…”
Section: Occludinmentioning
confidence: 92%
“…Occludin has four known splice variants (52), and knockout studies of the parent molecule have indicated its importance in tight junction stability and maintenance in epithelial cells (53). Additionally, occludin has been established as a regulator of epithelial cell migration, with phosphorylation at the Y473 residue resulting in PI3K activation at the leading edge of migratory cells (54).…”
Section: Occludinmentioning
confidence: 99%